MATHEMATICAL FORMULATION OF PLASTIC CHARACTERISTICS OF WIRE OF STEEL 70 AT HIGH-SPEED WIRE DRAWING - Yu. L. Bobarikin; S. V. Avsejkov (Литьë и металлургия)
The carried out numerical experiments subject to initial and boundary conditions indicate that mathematical model of elastic-plastic characteristics of steel 90 can be used for numerical calculations of wire drawing routes for this grade of steel.